Overview of Recent Advances in Canine Parvovirus Research: Current Status and Future Perspectives - Hongzhuan Zhou; Kaidi Cui; Xia Su; Huanhuan Zhang; Bing Xiao; Songping Li; Bing Yang (Microorganisms)
Canine parvovirus (CPV-2) was first identified in the late 1970s and has since become one of the most significant infectious agents affecting dogs. CPV-2 causes severe diseases such as hemorrhagic gastroenteritis and myocarditis, posing a major threat to canine health, particularly with a high mortality rate in puppies. It is globally recognized as a highly contagious and lethal pathogen. CPV is prone to rapid mutation, leading to the emergence of new variants. Despite widespread vaccination efforts, CPV remains one of the primary causes of acute gastroenteritis and death in young and juvenile dogs. Furthermore, the detection of CPV in swine populations has introduced additional challenges to its control. This review summarizes the current epidemiological status of CPV, highlighting recent advancements in diagnostic techniques and vaccine development. Additionally, it discusses the latest research on the pathogenesis of the virus and the development of antiviral agent research and proposes prevention and control suggestions for CPV under the One Health concept. In particular, there is a need to enhance surveillance of viral dynamics, accelerate the development of novel vaccines, and deepen the exploration of the underlying pathogenic mechanisms. This review aims to provide a scientific foundation for effective control of CPV and to guide future research directions.